Evaluation of the Effect of a Tracheal Stent on Radiation Dose Distribution via Micro-CT Imaging - Lin, Tao (Technol Cancer Res Treat, 2019)
PURPOSE: To study the effect of a metal tracheal stent on radiation dose distribution. METHOD: A metal tube bracket is placed in a self-made foam tube sleeve, and micro-computed tomography scanning is performed directly. The foam sleeve containing the metal bracket is placed in a nonuniform phantom for a routine computed tomography scan. The stents in conventional computed tomography images are replaced by the stents in micro-computed tomography images. Subsequently, 2 sets of computed tomography images are obtained and then imported to a radiotherapy treatment planning system. A single photon beam at 0° is designed in a field size of 10 cm × 10 cm, a photon beam of 6 MV, and a monitor unit of 200 MU. Monte Carlo algorithm is used to calculate the dose distribution and obtain the dose curve of the central axis of the field. The dose is verified with thermoluminescence dose tablets. RESULTS: The micro-computed tomography images of the tracheal stent are clearer and less false-like than its conventional computed tomography images. The planned dose curves of the 2 groups are similar. In comparison with the images without any stents in place, the doses at the incident surface of the stent in the conventional computed tomography images and at the stent exit surface in the rear of the stent increase by 1.86% and 2.76%, respectively. In the micro-computed tomography images, the doses at the incident surface of the stent and at the exit surface behind the stent increase by 1.32% and 1.19%, respectively. Conventional computed tomography reveals a large deviation between the measured and calculated values. CONCLUSION: Tracheal stent based on micro-computed tomography imaging has a less effect on radiotherapy calculation than that based on conventional computed tomography imaging.